2005
DOI: 10.1213/01.ane.0000140239.43116.30
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Integrity of Platelets in Volume-Reduced Platelet Concentrates

Abstract: Premature and low-birth-weight infants usually require small-volume platelet transfusions to treat thrombocytopenia. Also, infants undergoing open-heart surgery with extracorporeal circulation and with compromised cardiac function are at risk for excessive intravascular volume. The small-volume platelet substitution can be achieved by dispensing an aliquot from the unit of a standard single-donor platelet concentrate (PC). Alternatively, there is an indication for volume reduction of PCs to maximize the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…7 Furthermore, volume reduction of LR-ADP, a common practice in neonatal and pediatric transfusion medicine, has been reported to result in increased spontaneous in vitro PLT activation with resultant decreased aggregability. 16 Still, another publication has shown that PLT components with altered volumes maintained under original storage conditions have acceptable pH concentrations with the current FDA and AABB standards and have no significant difference in the improvement of posttransfusion PLT increments when compared to unaltered volume products, suggesting that these manipulated products may be as efficacious. 17 Despite impaired aggregation in vitro, transfusion of PLTs with metabolic derangements accrued over 5 days of storage has resulted in recovery of PLT function in vivo.…”
Section: Table 1 Metabolic Characteristics Of Residual Volumes Of Lrmentioning
confidence: 99%
“…7 Furthermore, volume reduction of LR-ADP, a common practice in neonatal and pediatric transfusion medicine, has been reported to result in increased spontaneous in vitro PLT activation with resultant decreased aggregability. 16 Still, another publication has shown that PLT components with altered volumes maintained under original storage conditions have acceptable pH concentrations with the current FDA and AABB standards and have no significant difference in the improvement of posttransfusion PLT increments when compared to unaltered volume products, suggesting that these manipulated products may be as efficacious. 17 Despite impaired aggregation in vitro, transfusion of PLTs with metabolic derangements accrued over 5 days of storage has resulted in recovery of PLT function in vivo.…”
Section: Table 1 Metabolic Characteristics Of Residual Volumes Of Lrmentioning
confidence: 99%
“…94 There is no standard method for preparing volume-reduced platelet concentrates. [80][81][95][96][97][98][99] If secondary volume reduction of platelet components is necessary, the authors recommend the method of Moroff and colleagues. [80][81][95][96][97][98][99] If secondary volume reduction of platelet components is necessary, the authors recommend the method of Moroff and colleagues.…”
Section: Secondary Volume Reductionmentioning
confidence: 99%
“…Although reported methods exist to reduce the volume of PLT concentrates when truly warranted (i.e. many PLT transfusions anticipated in which multiple doses of passive anti‐A or –B can not be avoided), additional processing should be performed with great care because of probable PLT loss, clumping, and dysfunction caused by the additional handling [1,11,12]. If a reasonable immediate post‐transfusion blood PLT count is not achieved by transfusing 10 ml/kg of unmodified PLTs and infusing a larger volume (e.g.…”
Section: Platelet Product To Transfuse Infantsmentioning
confidence: 99%